KEPEMIMPINAN KELUARGA DALAM KAJIAN KONTEKSTUAL: (TELAAH PERSPEKTIF NORMATIF FILOSOFIS) - Abdul Mujib Nasution (Yinyang: Jurnal Studi Islam Gender dan Anak, 2012)
Abstract: This paper in titled: Leadership Family In Contextual Studies: (Normative Perspectives Philosophical Studies). Through this paper try to reveal the problems of leadership in the family by examining the letter an-Nisa (4): 34dan al-Baqarah (2): 228. In the two verses in the letter an-Nisa and al-Baqarah, explained that the leadership be in the family was left to men. So in this paper about the leadership of the family are discussed through contextual studies using normative-philosophical approach. Normative approach is done by looking at the letter an-Nisa (4:34) and the letter al-Baqarah (2: 228) who became the theological foundation of men as leaders in keluarga. Untuk, various interpretations of scholars also described to determine the understanding them to verse. Philosophical Pendektan used among other things to see in the middle of family problems and how best memposisikannnya modernity amid the currents of modernity. Kata kunci: kepemimpinan, keluarga, dan hukum keluarga.